Effect of irrigation with magnetized water and spraying with humic acid on the vegetative and flowering growth characteristics of the rose plants (Elida). - Inas Yashar Jabbar; Alaa Hussein Abdel Qader (Zien Journals, 2022)
This experiment was carried out in the wooden canopy of the Department of Agriculture, with a percentage of 50% shading, located at latitude (35.456) and longitude (44.388), Kirkuk during the period from 1/6/2020 to 1/6/2021 in order to monitor the growth of the hybrid rose plant during a whole year. In the city of Kirkuk observing the effect of the study of magnetized water and spraying with humic acid on the vegetative and flowering growth characteristics of the Elida rose plant. Humic concentration (0, 2.5, 5) g. Liter-1 and by four sprays, the experiment was implemented using the RCBD randomized complete block design with three replications, and one experimental unit contained four plants. The results showed that both intensities of magnetized water 900 and 1800 gauss were significantly superior to the comparison treatment in terms of plant height, and the fresh weight of the root system, which amounted to (75.55 cm and 75.33 cm). And 42.33 g and 45.10 g), respectively. The highly treated plants exceeded 1800 gauss in a number of leaves, fresh weight of shoots, flower diameter, which amounted to (48.22 leaves. Plant-1, 89.99 g, 7.76 cm), respectively, The two concentrations of humic acid (2.5 and 5 g.l-1 ) were superior in plant height, flower diameter and reached (71.77 cm, 79.77 cm, 7.14 cm, 7.5 cm), respectively, when using a concentration of 5 g. L-1 significantly increased the number of leaves, the fresh weight of the vegetative group, and the fresh weight of the root system of plants, reaching (45.11 leaves. Plant-1, 83.11 g, 47.99 g), respectively.
Keywords: rose plant; magnetized water; humic acid